Estudo de viabilidade para construção de uma realidade virtual para o Arquivo Público do Estado do Pará - FERREIRA, Luiz Carlos Lourinho (2024)
Archives, as well as their collections, can benefit from Virtual Reality as a form of dissemination. In particular, museums stand out in using this technology to bring the public closer to the collection, something that can also be related to archives. Especially in locations far from large urban centers, Virtual Reality can be a key factor in the insertion of these populations into the cultural and scientific circuit - a context in which the state of Pará is inserted not only due to its geographic dimension, but also due to the difficulty of traffic, due to the fact that a large part of its territory is formed by the Amazon Rainforest. Although the collections in the capital Belém are easily accessible - as it is a metropolitan region - the continental size of the country must be considered, making the cost of transit between the regions somewhat impeding or difficult for researchers and, especially, Brazilian students. The objective of the research is to carry out a feasibility study to propose a preliminary structure model for the creation of a virtual environment similar to the physical one of an archival institution that allows the user to experience a simulation of reality. The research universe studied is archival institutions and their insertions in the virtual environment. As a sample, the Public Archive of the State of Pará was demarcated as a physical structure. For virtual environments, the possibility of using Virtual Reality devices and already available models applied in other virtual spaces was researched. This is research with a qualitative approach and of an applied nature. As for the objectives, it is descriptive with an exploratory research procedure and is divided into three stages. The first brings a survey of physical space characteristics with the objective of defining the characteristics of the environment of the Public Archive of the State of Pará. In the next stage, computational studies on Virtual Reality, use of software and hardware, forms of interaction, user immersion and engagement, the 3D environment and its integration with the virtual world - the entire system that a physical location could implement. In the third stage, the possibility of creating and inserting a virtual file is discussed, using technological procedures delimited in the second stage. The results demonstrate that, despite few studies of this type of application, the Public Archive of the State of Pará can, in principle, apply Virtual Reality through the use of a 360º camera, transforming the captures into a non-interactive video on platforms of online dissemination. Secondly, you can use the captures to build interactive environments. It is concluded that it is still a preliminary process and requires studies that focus on the application of Virtual Reality in these environments